Opinion of Bangladeshi teachers and undergraduate clinical students regarding the course duration of BDS curriculum - Ahmad, Md Rasel; Ara, Iffat; Talukder, Md Humayun Kabir; Hossin, Md Immam; Harun, Md Abdullah Al; Chowdhury, Dipak Kumar Paul; Faruque, Mohammad (Bangladesh Journal of Medical Education, 2017)
Background: Curriculum planning and designing is not a static process, rather a continuous process done regularly through a system. More than one decade have elapsed since the Centre for Medical Education (CME), in 1988, developed a national Undergraduate Dental Curriculum which was supposed to be community-oriented and competency based. The curriculum was partially implemented with the advancement of dental health science and application of newer techniques in dental practices in developed and developing countries. Rationale: A healthcare curriculum must be up-to-date, fit for purpose and relevant to the population it serves wherever that population might be, worldwide. It needs to assess the general and dental health needs of our local population and to propose a set of core skills of the dentists will need on graduation and in the future. The Health Science including Oro-dental science is changing with the advancement of health science, educational science & applied technology. Global changes are happening in health science and dental education in accordance and conformity of these advancements and changes. With the application of these knowledge and skills of dental science, future dentists should satisfy their patients with the changing needs of the community. The need to develop a community-oriented and competency-based curriculum was felt by all concerned. Objectives: The present study was undertaken to identify the Opinion of Bangladeshi teachers and undergraduate clinical students regarding the course duration of BDS curriculum. Methods: This descriptive type of cross sectional study was conducted in seven public and private dental colleges of Bangladesh after getting written permission from the principal of the respective dental colleges. Voluntary participation of the students was ensured and the names of the students' as well as teachers were kept confidential. The teachers and students of final years from the different dental colleges were the study population; among them four hundred (400) students and one hundred twenty teachers (120) were taken as sample by convenient sampling. Data collection instrument was a semistructured questionnaire with 5-point Likert scale for final year students' and in depth interview was used for teachers. Results: The study revealed that the 98% teachers mentioned that the course duration (4 years) in comparison to number of subjects and contents was not adequate and 98% teachers' opinion was that the total course duration should be 5 years. Nearly 75% of students mentioned that the total course duration should be 5 years. Conclusion: In this study, the students reported that they have acquired greater practical and clinical experiences in few areas from the curriculum of BDS course. The majority of the students were not satisfied on their acquired competencies in most of the areas after their graduation. This was due to shortage of course duration in comparison to number of subjects and contents, improper distributions of the subjects, inadequate duration of community placement, less allocation of hours in practical and clinical classes etc. Bangladesh Journal of Medical Education Vol.8(1) 2017: 18-21